Behaviour of human dental pulp stem cell in high glucose condition: impact on proliferation and osteogenic differentiation. (October 2020) - Kichenbrand, Charlene; Grossin, Laurent; Menu, Patrick; Moby, Vanessa
Highlights: High glucose did not modify dental pulp stem cell proliferation and viability. High glucose did not impair dental pulp stem cell osteogenic differentiation. Dental stem cells seem to display a resistance against high glucose conditions. Abstract: Objective: The aim of this study is to investigate the changes of human dental pulp stem cell (hDPSC) viability, proliferation and osteogenic differentiation in high glucose condition. Design: After 21 days of culture in low (5.5 mM) and high (20 mM) glucose medium, hDPSC viability and proliferation were assessed with respectively the 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) and Hoechst assays. To investigate the influence of glucose on osteogenic differentiation hDPSCs were cultured for 28 days in low or high glucose medium with osteoinductive cocktail. Mineralization was examined by alizarin red staining/quantification and the expression of osteogenic-related genes [ Runt-related transcription factor 2 ( RUNX2), Osteocalcin (OCN), Collagen 1A1 (COL1A1) ] analyzed by RT-qPCR. Results: We observed no significant difference ( p > 0.05) on hDPSC proliferation or cell viability between low or high glucose groups. We did not highlight a significant difference after alizarin red staining and quantification between hDPSCs cultured with high or low glucose concentration in the culture medium. In the same manner, high glucose concentration did not appear to modify osteogenic gene expression: there was no significant difference in osteogenic-related gene expression between high or low glucose groups. Conclusion: Proliferation, viability, and osteogenic differentiation of hDPSCs were not changed by high glucose environment.